Gospel and Scripture: Rethinking Canonical Unity - Watson, Francis (Tyndale bulletin, 2001)
It is widely believed that the Christian Bible is merely an anthology of the religious literature of ancient Israel and the early church, and that to speak of its ‘unity’ or ‘coherence’ is no longer possible. But biblical unity is still an issue where one seeks to understand the texts in their relation to God, and there are two main ways in which this issue is typically presented: biblical unity may be grounded in the process of divine inspiration which is believed to have generated these writings, or it may be grounded in a theory of providential ordering. The problem with both approaches is that they fail to reflect on the relation between scripture and the gospel, the proclamation of what God has done in and through Jesus and his Spirit which, for Christians, lies at the centre of the testimony of both Old and New Testaments. In his letter to the Galatians, Paul struggles to articulate an evangelical hermeneutic for scriptural interpretation, over against opponents who hold no less ‘high’ a doctrine of scripture than he does. This evangelical hermeneutic is not simply imposed on the texts from the outside, but identifies fundamental elements in the dynamics of these texts, notably the promise/law polarity. In broad outline, Paul’s argument can serve as a model for our own attempts to rethink scriptural unity.